Effects of adding enzymes to diets containing high levels of dried distillers grains with solubles on growth performance of finishing pigs - Jacela, J.Y.; Prusa, K.J.; Tokach, Michael D.; DeRouchey, Joel M.; Goodband, Robert D.; Nelssen, Jim L.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
A total of 1,032 pigs (BW = 101.5 lb) were used in a 90-d experiment to determine the effects of adding enzymes to diets containing high levels of dried distillers grains with solubles (DDGS) on growth performance and carcass characteristics of finishing pigs. Pigs were blocked by BW and randomly allotted to 1 of 7 dietary treatments with 6 pens per treatment. The control diet contained 30% DDGS. The remaining treatments were arranged in a 2 × 3 factorial design based on DDGS (45 or 60%) and enzyme inclusion (none, product A, or product B). Enzyme products were commercially available and designed for use in swine diets containing DDGS. Pigs allotted to the 60% DDGS treatment were fed 45% DDGS during the first 2 wk of the experiment to acclimate the pigs to DDGS. The 4 heaviest pigs from each pen were sold at d 78, and DDGS levels for all treatments were decreased to 20% until the end of the trial. Overall (d 0 to 90), enzyme supplementation did not affect ADG (P > 0.24), ADFI (P > 0.30), or F/G (P > 0.52). From d 0 to 78, regardless of enzyme treatment, ADG decreased (linear; P < 0.05) as DDGS increased because of a reduction (quadratic; P < 0.04)in ADFI. After topping and adding Paylean to the diets at d 78, ADFI tended to increase (linear; P< 0.06) in pigs previously fed 45 and 60% DDGS. However, the decrease in ADFI from d 0 to 78 still resulted in an overall reduction (linear; P < 0.04) with increasing DDGS. Increasing DDGS did not affect (P > 0.17) overall ADG, F/G, or final weight. There were no differences in carcass weight and yield (P > 0.65) or in backfat, loin depth, percentage lean, and fat-free lean index (P > 0.38) after adjusting to a common carcass weight. Increasing dietary DDGS increased (linear; P < 0.01) iodine value of belly fat (77.2, 83.7, and 87.3 g/100 g, respectively). This study indicates that up to 60% DDGS may be added to pig diets without negatively affecting growth performance or carcass traits compared to 30% DDGS when levels are reduced to 20% for 12 d before market; however, fat iodine values will be significantly increased. Neither commercially available enzyme product had any effect on pig growth performance.
Keywords: Enzyme; Dried distillers grains with solubles; Swine